2016
DOI: 10.4103/2278-330x.179701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of cytosine deletion of exon 5 of P53 gene in non small cell lung cancer patients

Abstract: Aim:Lung cancer is considered to be the most common cancer in the world. In humans, about 50% or more cancers have a mutated tumor suppressor p53 gene thereby resulting in accumulation of p53 protein and losing its function to activate the target genes that regulate the cell cycle and apoptosis. Extensive research conducted in murine cancer models with activated p53, loss of p53, or p53 missense mutations have facilitated researchers to understand the role of this key protein. Our study was aimed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other hand, p53 is the most frequently studied molecular mutation in human cancer, and p53 protein expression has been found in more than 50% of human tumors. The p53 is a tumor suppressor gene, which plays a negative regulatory role in cell proliferation and differentiation,[ 4 5 ] thus suggesting that aberrant p53 expression is a prerequisite for tumor development.…”
mentioning
confidence: 99%
“…On the other hand, p53 is the most frequently studied molecular mutation in human cancer, and p53 protein expression has been found in more than 50% of human tumors. The p53 is a tumor suppressor gene, which plays a negative regulatory role in cell proliferation and differentiation,[ 4 5 ] thus suggesting that aberrant p53 expression is a prerequisite for tumor development.…”
mentioning
confidence: 99%
“…It locates on the short arm of human chromosome 17 and encodes a nuclear phosphoprotein4. It is reported that the p53 gene is mutated in 50% to 70% of patients with lung cancer5, which plays a crucial function in cell cycle regulation, genomic stability, stress induced reaction and DNA repairing4.…”
mentioning
confidence: 99%
“…It locates on the short arm of human chromosome 17 and encodes a nuclear phosphoprotein4. It is reported that the p53 gene is mutated in 50% to 70% of patients with lung cancer5, which plays a crucial function in cell cycle regulation, genomic stability, stress induced reaction and DNA repairing4. The point mutations on exons 3–9 and 5–8 are mainly common mutations of p53 gene in lung cancer; especially the point mutation on exons 5–8, has been observed in 40–50% of non-small cell lung cancer (NSCLC)6.…”
mentioning
confidence: 99%